Cognitive Representation in the Biography of Naguib Mahfouz: An Approach in the Light of Cognitive Rhetoric - Swaileh, Fawzi Ali Ali Ali (Arts for Linguistic & Literary Studies, 2023)
The aim of this research is to examine how Naguib Mahfouz portrays the self and its concerns in narratives in his book "Echoes of Biography". The study is rooted in a cognitive perspective that is reflected in the narrative structure of the book. Mahfouz presents his work as a creative piece, and this justifies its inclusion in the research. The study is divided into an introduction and two main sections. The first section explores cognitive representation in its various forms, such as realistic, metaphorical, and symbolic representation. The second section examines the characteristics of perceptual rhetoric, including diagnosis, uniformity, and paradox. Together, these sections provide a systematic overview of the cognitive approach and its rhetorical features. The research concludes that the cognitive approach is an important tool for exploring texts and discourses and understanding the implicit mental systems that underlie them. Through this approach, we can gain insight into how humans perceive their relationship with the world and with each other, as well as the location of these relationships within the larger universe.